Community Empowerment to Create Healthy Villages Free of Stunting Through the Implementation of a Mobile Application to Monitor Breast Milk Expenditure and Adequacy for Babies - Agung Suharto; Nana Usnawati; Astin Nur Hanifah (Frontiers in Community Service and Empowerment, 2026)
Stunting is a condition of growth failure in children due to chronic malnutrition, especially in the first thousand days of life. Stunting affects brain growth and development. Reducing stunting requires integrated interventions including specific nutritional interventions, integrated pregnancy care, maternal nutrition monitoring, anemia monitoring, child growth and development monitoring, exclusive breastfeeding, provision of nutritionally adequate complementary foods, family empowerment to monitor the provision of Fe tablets for pregnant women, vitamin A for toddlers, PHBS, use of iodized salt, monitoring consumption of street snacks. This community service method is education about community empowerment to create a healthy village free from stunting through the implementation of a Mobile Application for monitoring breast milk expenditure and sufficiency for babies. The targets of this community service activity are breastfeeding mothers, posyandu cadres and community leaders. The results showed an increase in knowledge about stunting prevention. The results of statistical analysis obtained a p value = 0.000 (p <0.05) there was an increase in knowledge before and after being given education about the use of mobile applications to monitor breast milk expenditure and sufficiency proven effective in supporting stunting prevention. Conclusion: Community empowerment through the use of mobile applications to monitor breast milk expenditure and sufficiency has proven effective in supporting stunting prevention